Congenital diaphragmatic hernia: influence of associated malformations on survival. Issue 1 (July 1993) - Sweed, Y; Puri, P
Abstract : The medical records of 116 consecutive cases of congenital diaphragmatic hernia (CHD) among 368, 772 live births at the three maternity hospitals in Dublin were examined and the incidence of associated malformations and their impact on survival analysed. The patients were divided into two groups: group I included 64 (55%) patients who died during resuscitation and stabilisation before surgery at a mean age of 11.2 hours and group II included 52 (45%) patients who were operated upon. All patients in group I underwent detailed postmortem examination as did the 45% patients who died in group II. The mean (SD) gestational age for group I patients (36.1 (4.5) weeks) was significantly lower than the mean gestational age of group II patients (39.0 (2.4) weeks). Similarly, the mean birth weight of group I patients (2415 (906) g) was significantly lower than that of group II patients (3140 (563) g). Of the newborns who died before surgery, 40 (62.5%) patients had 79 associated malformations. The major associated anomalies were: cardiac (n = 16), neural tube defects (n = 15), skeletal (n = 8), chromosomal (n = 5), urinary tract (n = 6), gastrointestinal (n = 3), omphalocele (n = 4), craniofacial (n = 5), pulmonary (n = 2), and syndromes (n = 2). Sixteen (40%) of these patients were found to have multiple anomalies. Of the 52 patients who were operated upon, only four (7.7%) had associated malformations. Our data shows that associated malformations in neonates with CDH is a major factor influencing outcome in this congenital malformation.